2012
DOI: 10.1038/jid.2012.152
|View full text |Cite
|
Sign up to set email alerts
|

HLA-A*0201 + Plasmacytoid Dendritic Cells Provide a Cell-Based Immunotherapy for Melanoma Patients

Abstract: Several sources of evidence suggest that tumor-specific T cells have the potential to control melanoma tumors. Current active and adoptive therapeutic approaches to elicit such T cells are either not sufficiently clinically efficient or require fastidious processes that impede their extensive clinical use. As plasmacytoid dendritic cells (pDCs) have a crucial role in triggering antitumor immunity especially in melanoma, we explored their potential as a cell-based approach for melanoma immunotherapy. An irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 51 publications
1
48
0
Order By: Relevance
“…Along similar lines, the research group lead by Nadege Goutagny (Léon Bérard Research Center, Lyon, France) has demonstrated that the intratumoral administration of TLR7 agonists can restore the ability of pDCs to drive a robust, Type I IFN-dependent tumor-specific immune response 259 . Together with the clinical and preclinical results published by Tel and colleagues, 240 , 260 these results might pave the way toward harnessing the immunostimulatory potential of pDCs for anticancer immunotherapy 261 , 263 , 335 , 336 …”
Section: Literature Updatementioning
confidence: 85%
See 1 more Smart Citation
“…Along similar lines, the research group lead by Nadege Goutagny (Léon Bérard Research Center, Lyon, France) has demonstrated that the intratumoral administration of TLR7 agonists can restore the ability of pDCs to drive a robust, Type I IFN-dependent tumor-specific immune response 259 . Together with the clinical and preclinical results published by Tel and colleagues, 240 , 260 these results might pave the way toward harnessing the immunostimulatory potential of pDCs for anticancer immunotherapy 261 , 263 , 335 , 336 …”
Section: Literature Updatementioning
confidence: 85%
“…At least apparently, this is at odds with the association between high intratumoral levels of pDCs and poor disease outcome, which holds true in patients affected by several tumor types 32 , 96 , 99 , 100 , 259 . Thus, contrarily to previous beliefs, it may be possible to harness not only cDCs, but also pDCs, for anticancer immunotherapy 260 - 263 …”
Section: Literature Updatementioning
confidence: 99%
“…Plasmacytoid DCs (pDCs) are another interesting DC subset, also playing a critical role in shaping and regulating immune responses [25,26]. pDCs appear as novel vectors for immunotherapy for both cancer and infections [27][28][29][30], but their ability to cross-present SLP has never been investigated. Nonetheless, there is increasing evidence that pDCs effectively capture, process, and present antigens to T cells [31], including soluble and particulate antigens [32], lipopeptides and cell-associated antigens from apoptotic cells [33], viral particles [34], viral antigens from influenza-exposed cells [35] and tumour antigens (NY-ESO1) from measles virus infected tumour cells [36].…”
Section: Introductionmentioning
confidence: 99%
“…Two different approaches using PDC have been developed. A leukemic cell line with PDC characteristic has been isolated and, after having demonstrated functional activity in humanized murine models (140) and with melanoma PBL in vitro (141) will be evaluated in a clinical trial in HLA-matched melanoma patients (NCT01863108). In contrast, de Vries and co-workers have employed autologous, patient-derived PDC in a phase I clinical trial against melanoma (142).…”
Section: Improved Protocols For Dc-based Vaccination Against Cancermentioning
confidence: 99%